1980
DOI: 10.1002/path.1711300309
|View full text |Cite
|
Sign up to set email alerts
|

Stereological analysis of histological parameters in experimental premalignant hamster cheek pouch epithelium

Abstract: Hamster cheek pouch mucosa was treated with the carcinogen DMBA in order to provide samples of epithelium in the various pathological stages of carcinogenesis. Stereological techniques were applied to histological sections of normal and carcinogen-treated epithelium in order to quantify cytological and tissue parameters that may be related to the features of epithelial atypia. The results were compared with values previously obtained for benign epithelial hyperplasia induced by a solution of oil of turpentine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 35 publications
6
13
0
Order By: Relevance
“…In studies of carcinogenesis no single morphologic feature has yet been found completely to characterize the preneoplastic process. However, wc do agree with Franklin & Smith (10) in that the ability to ascribe numerical values to histologic fcatures that are usually only subjectively evaluated may indeed be useful in both diagnostic and research work.…”
Section: Resultssupporting
confidence: 59%
“…In studies of carcinogenesis no single morphologic feature has yet been found completely to characterize the preneoplastic process. However, wc do agree with Franklin & Smith (10) in that the ability to ascribe numerical values to histologic fcatures that are usually only subjectively evaluated may indeed be useful in both diagnostic and research work.…”
Section: Resultssupporting
confidence: 59%
“…[22] When group III and group IV ( P = 0.592) were compared, there was no significant difference with regard to cell area and NA and hence, N: C ratio was insignificant as well, whereas other studies by Franklin and Smith reported that the N:C ratio has the advantage of relating nuclear volume to cytoplasmic volume and possibly represents the significant changes that occur in the cell, more accurately at a morphological level. [23]…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Similar findings of an increase in nuclear size with dysplasia and squamous cell carcinoma have been reported in cervical smears and in experimental lesions in hamster cheek. 13 Thus, this increase in ND could be an early indication of malignant change 10,11 and case groups II and III were intermediate stages in the range from normal to carcinoma.…”
Section: Discussionmentioning
confidence: 93%
“…13 Thus, this reduction in CD could be an early indication of malignant change and these lesions can be considered as precancerous lesions. 10,11,12 Ramaesh et al reported a significant increase in the nuclear size in normal mucosal lesions with no dysplasia and further through dysplasias to squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%